Qualitative and Quantitative Analysis of Phytochemical Constituents of Alternanthera brasiliana (L.) Kuntze and Cassia alata (L.) using Different Organic Solvents - Khatri, Devika; Lawati, Amrit Maya (Himalayan Journal of Science and Technology, 2022)
The therapeutic qualities of Alternanthera brasiliana and Cassia alata are due to the phytochemicals contained in these plants. This research was conducted to study the phytochemical analysis of leaf extracts of these plants using methanol, hexane, and chloroform solvents. The leaves were collected, cleaned, and dried for eight hours at 60°C in a cabinet dryer. Using the solvent extraction method, the extract was made. Qualitative and quantitative analysis was done to determine the occurrence of flavonoids, terpenoids, tannins, phenols, amino acids, alkaloids, phlobatannins, glycosides, and saponins. The extraction yields in methanol, hexane, and chloroform were 15.77%, 3.01%, and 3.16% for A. brasiliana and 26.91%, 19.5%, and 18.32% for C. alata. Alkaloids, terpenoids, tannins, phenols, glycosides, flavonoids, carbohydrates, phlorotannins, and saponins were all found in A. brasiliana. Alkaloids, tannins, phenols, glycosides, flavonoids, carbohydrates, and saponins were found in C. alata. Total phenolic, flavonoid, and tannin content in methanol extract for A. brasiliana were found to be 127.76 mg GAE/g, 136.48 mg GAE/g, and 58.88 mg GAE/g. The total phenolic, flavonoid and tannin content found were 41.76 mg GAE/g, 103.21 mg GAE/g, and 58.67 mg GAE in hexane extract. Similarly, 102.4 mg GAE/g, 112.49 mg GAE/g, and 41.76 mg GAE/g in the chloroform extract. Total phenolic, flavonoid, and tannin content of C. alata in the methanol extract were 36.3 mg GAE/g, 22.43 mg GAE/g, and 10.89 mg GAE/g, in the hexane extract, 25.98 mg GAE/g, 16.68 mg GAE/g, and 3.25 mg GAE/g, in the chloroform extract, 28.52 mg GAE/g, 20.33 mg GAE/g, and 4.56 mg GAE/g. From extraction yields and qualitative and quantitative analysis, methanol was the best solvent.